Areas of improvement of the budgetary deficit of Ukraine - Vychurova, A. R. (ТДАТУ, 2019)
The purpose of this article is to identify the reasons of the state’s budget deficit and public debt as the main components of its financial system and to identify effective methods of managing public debt in the current state of the financial system of Ukraine.
Keywords: deficit; budget deficit; the financial situation